Raz on Rights: Human Rights, Fundamental Rights, and Balancing. (March 2017) - Zanghellini, Aleardo
Abstract: After clarifying the outlines of Raz's interest theory of rights and its relationship to aspects of the principles theory of rights, I consider how his recent observations on human rights manage to fit (or fail to fit) into the interest theory. I then address two questions. First, I elaborate on Raz's definition of morally fundamental rights, arguing that he is right in claiming that there are no such rights. I then show that the interest theory accommodates the notion that rights may take qualitative precedence over conflicting considerations—a question that has become increasingly relevant in light of recent writing on rights.